A STRATEGY-ORIENTED AND AGILE FRAMEWORK FOR MANAGING BUSINESS PROCESSES: A CASE STUDY ON E-BANKING - BOUFAIDA, M; OUAAR, H (Courrier du Savoir, 2018)
ABSTRACT The present paper provides a framework for developing a supervision system of business processes in enterprises. This methodology is based on a strategy-oriented architecture covering three phases: analysis, design and implementation. It combines concepts of the Balanced Score Card method, UML, Business Processes Execution Language for Web Services and of the agent paradigm. The proposed methodology aims to ensure the agility property that permits easily to change and refine the architecture elements without involving the other ones. In order to evaluate this framework, a prototype system has been developed with a case study related to the Algeria Gulf Bank, with showing its practical applicability through a simulation under the JADE platform.   Keywords: Business Processes, Enterprise Business Strategy, Monitoring, BSC, BPEL4WS, Agent, Agility.   RESUME Le présent document fournit un framework pour développer un système de supervision des processus métiers dans les entreprises. Cette méthodologie propose une architecture basée sur la notion de stratégie, couvrant trois phases: analyse, conception et implémentation. Elle combine des concepts de la méthode Balanced Score Card, UML, Business Processes Execution Language for Web Services et ceux du paradigme agent. La méthodologie proposée vise à assurer la propriété d'agilité permettant de modifier facilement et d'affiner les composants de l’architecture sans impliquer les autres. Afin d'évaluer les idées proposées, un prototype a été développé avec une étude de cas relative à l’AGB (Algeria Gulf Bank), afin de fournir son application grâce à une simulation via la plate-forme JADE. MOTS-CLES: Processus métiers, Stratégie métiers d'entreprise, supervision, BSC, BPEL4WS, Agent, Agilité.